2021
DOI: 10.3389/fimmu.2021.627605
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Mesenchymal Stromal Cells Exert Opposite Effects to Their Cells of Origin in Murine Sodium Dextran Sulfate-Induced Colitis

Abstract: Several reports have described a beneficial effect of Mesenchymal Stromal Cells (MSCs) and of their secreted extracellular vesicles (EVs) in mice with experimental colitis. However, the effects of the two treatments have not been thoroughly compared in this model. Here, we compared the effects of MSCs and of MSC-EV administration in mice with colitis induced by dextran sulfate sodium (DSS). Since cytokine conditioning was reported to enhance the immune modulatory activity of MSCs, the cells were kept either un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Similar results have been obtained with EV-mix released by murine BM-MSCs exposed to IL-6, TNF-α, and IL-1β, its administration in a murine model of colitis reduces the clinical-pathological signs of the disease. Reduction in the M1 marker iNOS and increase in the M2 marker CD163 is observed in the colon tissue, while in the intestinal lymph node the Treg/Teffectors ratio increases [117]. Moreover, the MVs obtained from 3D cultures of BM-MSCs exposed to ischemic brain extracts are enriched in immunoregulatory and angiogenic cytokines [111].…”
Section: Effect Of Cytokines On Ev-msc Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been obtained with EV-mix released by murine BM-MSCs exposed to IL-6, TNF-α, and IL-1β, its administration in a murine model of colitis reduces the clinical-pathological signs of the disease. Reduction in the M1 marker iNOS and increase in the M2 marker CD163 is observed in the colon tissue, while in the intestinal lymph node the Treg/Teffectors ratio increases [117]. Moreover, the MVs obtained from 3D cultures of BM-MSCs exposed to ischemic brain extracts are enriched in immunoregulatory and angiogenic cytokines [111].…”
Section: Effect Of Cytokines On Ev-msc Contentmentioning
confidence: 99%
“…Stimulation of MSCs with proinflammatory cytokines increases the amount of EVs released by these cells [117][118][119][120], and changes its content which influences their immunoregulatory capacity. In addition, EVs released by resting or activated BM-MSCs do not express MHC-I or MHC-II [98].…”
Section: Effect Of Cytokines On Ev-msc Contentmentioning
confidence: 99%
“…Many studies highlighted the ability of EVs to regulate immune cells and cytokines within the inflammatory microen-vironment, dampening inflammation and restoring the intestinal barrier integrity and gut microbiome composition and diversity [19]. Evidence of these EVs improving effects on IBD emerged from in vivo studies on a dextran sodium sulfate-induced IBD animal model, where MSC-derived EV administration decreased the disease severity, reducing inflammation and improving epithelial functions [32,33]. Some studies on EVs derived from food showed ameliorating properties on intestinal inflammation for those isolated from edible plants such as Curcuma longa, grapes, and broccoli [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bone marrow mesenchymal stem cells (MSC) reduced severity of colitis through secretion of TSG6, facilitating the accumulation of IL‐10‐producing macrophages 260 . In another work, the anticolitic role of MSCs was attributed to extracellular vesicles 261 . Similarly, exosomes from umbilical cord mesenchymal stem cells (UCMSCs) were able to suppress the infiltration of inflammatory macrophages and reduce their production of colitogenic cytokines, thus alleviating DSS colitis in mice 262 The exact component(s) responsible for the anticolitic effect of UCMSC‐derived exosomes still need to be further elucidated.…”
Section: Therapeutic Implications—from a Macrophage Perspectivementioning
confidence: 99%